Accountability For The Management Of School Assistance Funds (BOS) at MTs Ma’Arif NU 1 Jatilawang Banyumas Regency in 2019/2020 - Tursino Tursino; Chamid Sutikno; Shadu Satwika Wijaya (Department of Public Administration, University Wijaykusuma Purwokerto, 2022)
This studi ecaminwa the accountablility of the management of school operational assistance Funds (BOS) at MTS Ma’arif NU 1 Jatilawang Banyumas Regancy in 2019/2020. This study aims to determine vertical accountability and horizontak accountablility in the management of school operational assistance Funds at MTS Ma’arif NU 1 Jatilawang. The research was carried out using qualitative descriptive research that involves researchers in continuous and continuous experience with partisipans. Qualitative research is a research approach that tries to reveal specific meaning form each subject’s point of view subjectively and aim to explore the deepest meaning of the subject about a phenomena.The development of qualitative research as a research method in the context to problems regarding socail, cultural, and human behavior phenomena (Ahyar et al., 2020). In qulitative research, the researcher becomes the main instrument in collecting and interpreting the date obtained in the failed. The results of the study indicate that every madrasah has almost the same problems regarding financial accountability to the public, but the pettern of implementing the accountability system sill nedds to be improved, both vertical and heriizontallly. The role of madrasah in the context of accountability must be carried out formaterials for improving the accountablitity system that ensures the implementation of back to back madrasah governance.